EVALUATION OF THE ACTION OF TWO FLUORIDES SYSTEMS APPLIED TO DENTAL ENAMEL SURFACE, IN VITRO STUDY - Campuzano, Maria Chávez (2016)
Objective: To assess the action of two types of fluorides over dental enamel surface. Materials and methods: Extracted molars were randomly divided into 8 groups, comprising 7 experimental groups and one control group. Each molars from the experimental groups was treated in a sterile small container with artificial saliva and lactic acid for 48 hours. Saliva was changed and the teeth were put in contact with gel and varnish fluoride at different periods of time (2, 24, 26, 50, 52 hours). The molars from the control group receive no treatment. Data from measurements of pH and calcium absorption (CCa) were collected from the artificial saliva of each group at different periods of time, in contact with lactic acid and with both fluorides, weight was also measured. This data was analyzed through ANOVA (p < 0, 05) and the Tukey test. Results: The contact with lactic acid produced a great loss of calcium that decreased notably with two different fluorides used, without a significant stati